2012
DOI: 10.1111/j.1743-498x.2012.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical training in your hands: organising a skills course

Abstract: We recommend the organisation of skills courses to any trainee. By following key ground rules, the surgical trainee can enable the acquisition of advanced learning opportunities and the ability to demonstrate valuable organisational skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…One specific problem on this kind of activities is the attendance (9,10). Because of daily activities it is very difficult for professionals to take part of any post-graduate training instead they receive a specific authorization from their superiors.…”
Section: Discussionmentioning
confidence: 99%
“…One specific problem on this kind of activities is the attendance (9,10). Because of daily activities it is very difficult for professionals to take part of any post-graduate training instead they receive a specific authorization from their superiors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown favourable results with the implementation of specialty-specific skills courses [6,7]. In particular, a work-based structure with repeated episodes of training spaced out over weeks to months have been suggested as the most favourable format [8,9]. We aimed to develop and trial a self-titled "Registrar Academy" in the hope to better prepare residents…”
Section: Introductionmentioning
confidence: 99%
“…3,4 To resolve inexperience, possible medicolegal concerns, and potential risks for patients used by trainers as teaching subjects, it has been recommended that a large part of teaching and practice should occur outside the operating room. [4][5][6][7] Practicing transplantation surgery on relevant animal models is thus a widely used option for learning and practicing different techniques in a near-to-clinical scenario. 5,8 Besides the animal models, cadaveric training remains the gold standard before surgery on the live patient.…”
Section: Introductionmentioning
confidence: 99%